A case study of an integrated manufacturing performance measurement and meeting system. Issue 4 (5th May 2015) - Olivella, Jordi; Gregorio, Rubén
Abstract : Purpose: – The purpose of this paper is, first, to expose an integrated manufacturing performance measurement and meeting system implemented to focus the organization on value streams and, by doing it, to improve performance, and, second, to analyze the results obtained. Design/methodology/approach: – This paper is based on an exploratory case study carried out at Delphi Diesel Systems (DDS) plant in Sant Cugat (Spain). Findings: – The integrated manufacturing performance measurement and meeting system implemented by DDS Sant Cugat resulted in being very successful and appropriate to obtain the established objectives: focus the organization on value streams; and, by doing it, to improve performance, particularly the overall equipment effectiveness. Research limitations/implications: – Considering the limited amount of research on the subject this kind of exploratory research is considered to be appropriate. The main limitation is that a single manufacturing plant was analyzed. Even though the characteristics of the plant and the problems addressed are common and, in consequence, it can be thought that the experience is replicable, further research should be conducted to verify it. Practical implications: – For the management community, this paper provides a new way of designing and using manufacturing performance measurement systems. Originality/value: – The presented case confirms previous works stating the importance of how performance measures and meetings are used and the need of involvement of the whole organization. The joint planning of the performance measures and the meeting system that has been presented had not previously been analyzed by the literature.